Intravenous cannula care in the inpatient hospice setting. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Newens, Paula; Rowlstone, Theresa; Butler, Claire
Abstract : Background: There is little data on the subject of practical procedures in hospices. The Minimum Data Set, collected annually by the National Council for Palliative Care, recorded clinical interventions for the first time in 2008–2009. Response rates remain too few to draw conclusions. Anecdotally, there has been an increase in practical procedures with growth of the modern hospice movement. Bloodstream infections account for 7% of all healthcare associated infections (HCAI) in England and are associated with high level of patient mortality. Around 44% of these infections are directly attributable to invasive devices. It has been estimated that each HCAI costs the NHS £4, 300 totalling at least £1 billion. Aims: To assess current practice of insertion and ongoing care of intravenous cannulae in the inpatient hospice setting. To develop new strategies to promote best practice guidelines. Methods: The documentation relating to 10 consecutive intravenous cannula insertions was recorded prospectively at an inpatient specialist palliative care unit. Ward staff were blinded to this to minimise observation bias. Documentation for each cannula was assessed retrospectively against NHS guidelines and standards. New documentation was developed. Following a trial period, the insertion and ongoing care of cannulae were reaudited across the organisation, comprising three inpatient specialist palliative care units. Twenty consecutive cannulae were recorded and assessed retrospectively. Results: The initial audit showed an average of 14.7% compliance with the national guidance which increased to 68.6% after the introduction of the new documentation. The Mann–Whitney test suggested a statistically significant (p=0.0006) improvement in recording of cannula care. Conclusion: It is important that evidence-based guidance is used across all areas of healthcare to improve patient care. Introduction of a quick, simple, self-contained recording system can produce a significant increase in the evidence of good cannula care.